Speech Recognition for Cleft Lip and Palate Voice and Standard Voice for Consonant Words /B/ - Akhmad Anggoro; Samiadji Herdjunanto; Risanuri Hidayat (SENATIK STT Adisutjipto, 2019)
Advances in technology make speech recognition improve. But does speech recognition recognize the sounds of cleft lip and palate? this research uses the voice of cleft lip and palate to normal voice. With the letter / b / which is the letter for lip articulation. Words used include Clothes, Ash and Moist. The extraction method uses Mel Frequency Cepstral Coefficients (MFCC), the classification uses K-Nearest Neighbor (KNN) with K-Fold Cross-Validation as a test. The results show the accuracy above 70%. 75% in the word "Baju". 75% in the word "Abu". 83% in the word "Lembab".